Implementação de automatismo na transferência e análise de dados de monitorização do helicóptero EH101 - Nunes, Marco (2022)
Júri: Presidente: MGen/EngAer/020829-K Pedro Miguel de Palhares Veloso da Silva;Orientador: Professor Doutor Filipe Szolnoky Ramos Pinto Cunha; Co-orientador: Cap/EngAer/128671-E Marco Filipe Morais Pinto;Vogais: TCor/EngAer/100874-K Ana Rita Duarte Gomes Simões Baltaza